Political Allegory in: Salman Rushdie’s Midnight’s Children - Moussaoui, Ouafa (University of El-oued, 2021)
Midnight’s Children is a loose allegory for events in India both before and after the independence and partition of the Indian nation which took place at midnight on 14th August 1947.The novel is considered as an example of post-colonial literature. The aim of the study is to analyze how political allegory operates as an extended metaphor in which symbolic actions, characters, settings and images serve to reflect complicated issues that cannot be expressed explicitly. This research is conducted by using qualitative research and descriptive method to interpret and analyze the data. The main data are the facts and information about post-colonial issues through selected events and characterizations in the Midnight’s Children. The findings of the study prove that political allegory as an apparatus helps in re-evaluating and re-examining the history to find a solution and to create a harmonious and well-balanced society.
Keywords: Midnight’s Children, Allegory, Political, History, Post-colonial literature.